2012
DOI: 10.3109/10715762.2012.692784
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade chronic inflammation and superoxide anion production by NADPH oxidase are the main determinants of physical frailty in older adults

Abstract: Physical frailty in older people is associated with superoxide anion overproduction by NADPH oxidase and low-grade chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…For example, the increased oxidative stress that has been observed in frail older adults has been hypothesized to arise from mitochondrial dysfunction (Villamena and Zweier 2004). Consistent with this hypothesis is the study by Baptista et al (2012) showing that superoxide anion production was increased in white blood cells of frail older adults. Recently, it was also shown in blood that, lower mtDNA copy number, a marker that reveals mitochondrial depletion, energy reserves, and oxidative stress is associated with frailty (Ashar et al 2015).…”
Section: Introductionsupporting
confidence: 63%
“…For example, the increased oxidative stress that has been observed in frail older adults has been hypothesized to arise from mitochondrial dysfunction (Villamena and Zweier 2004). Consistent with this hypothesis is the study by Baptista et al (2012) showing that superoxide anion production was increased in white blood cells of frail older adults. Recently, it was also shown in blood that, lower mtDNA copy number, a marker that reveals mitochondrial depletion, energy reserves, and oxidative stress is associated with frailty (Ashar et al 2015).…”
Section: Introductionsupporting
confidence: 63%
“…44 However, because of their evanescent nature, they are difficult to measure directly in humans. 45 Superoxide anion overproduction was noted in isolated white blood cells of frail older adults, which further confirmed the association between oxidative stress and frailty. 45 Superoxide anion overproduction was noted in isolated white blood cells of frail older adults, which further confirmed the association between oxidative stress and frailty.…”
Section: Reactive Oxygen Species and Frailtysupporting
confidence: 53%
“…A number of observational studies have associated markers of oxidative stress or inflammation with measures of frailty such as slow gait speed. (71, 72) These studies have suggested that adiposity induces oxidative stress and thus grip strength(73) and that inflammation is associated with reduced grip strength and reduced walking speed in older subjects with the highest body fat percentage. (74) But it is also known that inflammation only partially explains observed mobility limitations.…”
Section: Discussionmentioning
confidence: 99%